PENGARUH PERBEDAAN PERILAKU BELAJAR KELOMPOK PEMINATAN DAN KELOMPOK LINTAS MINAT TERHADAP HASIL BELAJAR SOSIOLOGI DI KELAS XI SMAN 6 PADANG - Hanadia Marfita; Yenni Melia; Hefni Hefni (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The context for this study is the low sociology student learning results in Class XI SMA Negeri 6 Padang. The purpose of this study is to examine the impact of variations in learning behavior between students in specialized groups and students in cross-interest groups on sociology learning outcomes in sociology topics. This is a quantitative approach of study. The purposive sampling strategy was used in this investigation. Because these classes had the lowest average even midterm tests in sociology, the samples chosen were XI IPS 2 and XI MIPA 4. There were 69 students in all that participated in the research. The basic data in this study are the results of questionnaire distribution to respondents, namely class XI pupils specialized groups (IPS) and cross-interest groups (MIPA) Padang. Observation and questionnaires were used to collect data in this study. The t test is used in this study's data analysis approach. Based on the findings of the preceding study, it is possible to conclude that variations in learning behavior between specialty group students and cross-interest group students have an impact on sociology learning outcomes in Class XI SMA Negeri 6 Padang. This is supported by the t test findings, which show that t count (2.230) > t table (2.032).